High-Resolution Ultrasound-Assisted Assessment of Preliminary Short-term Safety Outcomes of an Implant-Based Augmentation Mammaplasty Using a Bioengineered, Cell-Friendly, Smooth-Surface Device in Korean Females - Sangdal Lee; Jeong Pil Jeong; Jung Youp Sung; Woo Sik Choi; Dong Seung Moon; Ho Chan Kim; Jae Hong Kim (Aesthetic Surgery Journal Open Forum, 2021)
Abstract BackgroundThe Motiva Ergonomix Round SilkSurface (Establishment Labs Holdings Inc., Alajuela, Costa Rica) is one of the representative brands of the fifth generation of a silicone gel-filled breast implant with a microtextured surface. ObjectivesIn this study, the authors describe preliminary short-term safety outcomes of an implant-based augmentation mammaplasty using the Motiva Ergonomix Round SilkSurface in Korean females. MethodsThe authors performed a retrospective analysis of medical records in a total of 69 females (n = 69) receiving an implant-based augmentation mammaplasty using the Motiva Ergonomix Round SilkSurface between September 26, 2017, and December 31, 2020. The authors analyzed incidences of postoperative complications. ResultsA total of 6 cases (8.7%) of postoperative complications occurred; these include 2 cases (2.9%) of early seroma, 1 case (1.4%) of capsular contracture, 2 cases (2.9%) of alterations in the shape, and 1 case (1.4%) of foreign body sensation. Time-to-events were estimated at 266.81 ± 273.17 days. ConclusionsThe authors describe our preliminary short-term safety outcomes of an implant-based augmentation mammaplasty using the Motiva Ergonomix Round SilkSurface in Korean females. But this deserves further large-scale studies with long periods of follow-up. Level of Evidence: 4